COLOR REVOLUTIONS AND THE INDIAN ECONOMY: रंगीन क्रांतियाँ एवं भारतीय अर्थव्यवस्था - Saxena, Anjana (International Journal of Research -GRANTHAALAYAH, 2014)
Colors not only express emotion, but they also symbolize development in the economy. The Indian economy is a direct proof of this. In a colorless economy, color revolutions have done the task of enhancing (developing) its beauty. Green, yellow, blue, golden, white, pink etc. adorned with many colors, the Indian economy is spreading its iridescent colors all around. History testifies that revolutions run with a great resolve and if the efforts are firm with them, they will surely succeed. Symbolic colors related to various objects appeared in the form of colorful revolutions combined with a resolution. रंग न केवल भावों की अभिव्यक्ति करते हैं वरन् वे अर्थव्यवस्था में विकास के प्रतीक भी हैं। भारतीय अर्थव्यवस्था इसका प्रत्यक्ष प्रमाण है। रंगहीन अर्थव्यवस्था में रंगीन क्रांतियों ने रंग भरकर उसका सौंदर्य निखारने (विकसित करने) का कार्य किया है। हरा, पीला, नीला, सुनहरा, सफेद, गुलाबी आदि कई रंगों से सजी भारतीय अर्थव्यवस्था अपने इंद्रधनुषी रंग चारों ओर बिखेर रही है। इतिहास साक्षी है कि क्रांतियाँ एक विराट संकल्प लेकर चलती हैं और उसके साथ यदि प्रयास दृढ़ हो तो वे निष्चित रूप से सफल होती है। विभिन्न वस्तुओं से संबंधित प्रतीकात्मक रंग एक संकल्प के साथ जुड़कर रंगीन क्रांतियों के रूप में प्रकट हुये।